Use of tranexamic acid for skin whitening and melasma therapy: A product review - Halimi Syafiqah Nadiah; Masood Hannah; Kah Seng Lee; Suhaidah Mohd Jofrry; Long Chiau Ming (Archives of Global Professionals, 2016)
Purpose: The aim of this study is to assess the usage of tranexamic acid as skin whitening and melasma therapy. Methodology: An electronic search on PubMed, MEDLINE and Cochrane Library with keywords "tranexamic acid," "oral," "systemic," "whitening," "lightening," and "melasma" was carried out. The literatures are summarized in the evidence tables. Further search on PBAC, UK, NFSA, SMC, CEDAC, MIMS, and Micromedex was performed for listing reviews of tranexamic acid. Results: The data available are not scientifically proven to demonstrate the role of tranexamic acid as an effective treatment for melasma therapy and whitening agent. Conclusions: As a conclusion, due to the lack of data, it was not possible to reach a conclusion on the use of tranexamic acid as cosmetic products, especially with systematic usage.